Mickey Rooney & Judy Garland collection. Strike up the band [videorecording (DVD)] - Berkeley, Busby, 1895-1976; Rooney, Mickey; Garland, Judy; Whiteman, Paul, 1890-1967 (Turner Entertainment Co. : Distributed by Warner Home Video, 2007)
Jimmy and Mary are two talented high school students ready and eager to climb the ladder of success. He's a band leader and she's his lovelorn singer. Together they sing and dance their way to the top, with a few bumps along the way.